An influenza A virus agglutination test using antibody-like polymers - Sukjee, Wannisa; Thitithanyanont, Arunee; Wiboon-ut, Suwimon; Lieberzeit, Peter A.; Paul Gleeson, M.; Navakul, Krongkaew; Sangma, Chak (My University, 2017)
Antibodies are commonly used in diagnostic routines to identify pathogens. The testing protocols are relatively simple, requiring a certain amount of a specific antibody to detect its corresponding pathogen. Antibody functionality can be mimicked by synthesizing molecularly imprinted polymers (MIPs), i.e. polymers that can selectively recognize a given template structure. Thus, MIPs are sometimes termed ‘plastic antibody (PA)’. In this study, we have synthesized new granular MIPs using influenza A virus templates by precipitation polymerization. The selective binding of influenza A to the MIP particles was assessed and subsequently contrasted with other viruses. The affinities of influenza A virus towards the MIP was estimated based on an agglutination test by measuring the amount of influenza subtypes absorbed onto the MIPs. The MIPs produced using the H1N1 template showed specific reactivity to H1N1 while those produced using H5N1 and H3N2 templates showed cross-reactivity.
Keywords: agglutination test; antibody-like polymers; influenza A virus; Molecularly imprinted polymers; plastic antibody